Role of ultrasonography in diagnosis of urological lesions: hospital based study - Panchmahalkar, Ameet C.; Khan, Shoeb; Salim, Wajahat (International Journal of Research in Medical Sciences, 2016)
Background: Ultrasound examination is considered to be a very useful imaging modality for the diagnosis of renal colic as well as other renal or extra-renal diseases. One of the major advantages of ultrasound examination is the avoidance of radiation exposure. However, it is reported to be operator dependent and less accurate when compared with Computed Tomography. Present study describes role of ultrasonography in assessment of suspected urological disease in patients referred to radiodiagnosis department of Nair Hospital, Mumbai during the study period. Methods: This observational descriptive study was conducted during June 2006 to June 2008 at Department of Radiology, BYL Nair Hospital, Mumbai, India. 84 patients with clinical features suggestive of urological disease and referred to the department for ultrasound examination were enrolled. Ultrasonography was done on a TOSHIBA ECCOCEE duplex Doppler ultrasound machine with 3.5-5 MHz curvilinear transducer. USG findings were correlated with the final diagnosis and USG examination findings were considered diagnostic if they resulted in correct histopathological diagnosis or correct identification of malignant tumours along with organ site. They were considered contributory when either the organ site was correctly identified without histology diagnosis or when malignancy was identified but without proper organ site. If the lesion was not detected, USG findings were marked as false negative and they were marked as false positive when the predicted disease was found to be incorrect on confirmatory diagnosis. Results: Age of the patients ranged from 0 to 76 years. Out of 84 patients studied, 49 were males and 35 were females. Overall ultrasound examination findings were found to be diagnostic in 48 cases (57.14%), contributory in 26 cases (30.95%), false negative in 10 cases (11.9%) whereas there were no false positive reports. There were 56 cases in which there were kidney lesions. Ultrasound examination findings were found to be diagnostic in 35 cases (62.5%), contributory in 17 cases (30.35%) and false negative in 4 cases (7.14%) whereas there were no false positive reports. There were 10 cases in which there were lesions involving both kidney and ureters. Ultrasound examination findings were found to be contributory in 8 cases (80%) and false negative in 2 cases (20%).There were 4 cases in which there were lesions involving ureters. Ultrasound examination findings were found to be false negative in all 4 cases (100%). There were 14 cases in which there were lesions involving urinary bladder. Ultrasound examination findings were found to be diagnostic in 4 cases (28.57%), contributory in 9 cases (64.28%) and false negative in 1 case (7.14%). Conclusions: Ultrasound examination was found to be diagnostic or contributory in diagnosis in most of the cases (88.1%). However there were a sizeable proportion of cases (11.9%) with false negative results on ultrasonography.